PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKAT HASIL BELAJAR IPS SISWA KELAS V SDN 43 LEMBAH KARILAM - Rahma Dani; Putri Zahara; Rahma Donal; Nurul Azizah; Nurul fauziah; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve elementary school students' social studies learning outcomes through the application of the Problem-Based Learning (PBL) model. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart design implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 28 fifth-grade students of SDN 43 Lembah Karilam. Data collection techniques included observation, tests, and documentation. The results showed that the application of the PBL model significantly improved students’ learning outcomes. In the pre-cycle, the average student score was 62.3 with a cpletion rate of 35.7%. After the first cycle, the average score increased to 71.5 with a completion rate of 60.7%, and in the second cycle, the average score reached 82.4 with a completion rate of 89.3%. The N-Gain score increased from the moderate category in the first cycle to the high category in the second cycle. Thus, the PBL model was effective in improving elementary school students' social studies learning outcomes.